2017
DOI: 10.14238/pi57.4.2017.194-7
|View full text |Cite
|
Sign up to set email alerts
|

Waist circumference and insulin levels in obese children

Abstract: Background Childhood obesity is one of the most serious public health challenges of the 21st century. Its prevalence has increased at an alarming rate. Overweight and obese children are prone to obesity in adulthood and to developing non-communicable diseases (NCDs) like diabetes and cardiovascular diseases at a younger age. Increased waist circumference has been shown to contribute to the risk of metabolic syndrome in obese adults. Objective To assess for a correlation between waist circumference and insulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In this study, waist circumference and WHtR were positively correlated with insulin and HOMA-IR. Previous studies have suggested that waist circumference is (Cempaka & Sidiartha, 2017) and HOMA-IR (da Silva et al, 2018;Lim et al, 2015). Waist circumference is more strongly correlated with HOMA-IR than with BMI (Convit et al, 2012).…”
Section: Discussionmentioning
confidence: 90%
“…In this study, waist circumference and WHtR were positively correlated with insulin and HOMA-IR. Previous studies have suggested that waist circumference is (Cempaka & Sidiartha, 2017) and HOMA-IR (da Silva et al, 2018;Lim et al, 2015). Waist circumference is more strongly correlated with HOMA-IR than with BMI (Convit et al, 2012).…”
Section: Discussionmentioning
confidence: 90%
“…In addition, one study found that children with p-DCD showed higher waist circumference, which indicates significantly higher levels of abdominal obesity [26]. A larger waist circumference can lead to a greater prevalence of health risks such as cardiovascular disease, insulin resistance, musculoskeletal disorders, some forms of cancer, and disability associated with increased weight [26][27][28][29]. Furthermore, only a few studies have examined the diverse aspects of health-related fitness among the same children with different levels of motor proficiency [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…[2] Prevalence of childhood obesity in Indonesia is 19.7% in boy and 32.9% in a girl. [4] The presence of obesity is associated with significant adverse effects on health including metabolic, endocrinology, cardiovascular, gastrointestinal, pulmonary, neurologic, psychiatric, hematologic, and skeletal complications, and development of some types of malignancies. All of these unfavorable effects lead up to a shortened lifespan.…”
Section: Introductionmentioning
confidence: 99%